The influence of built environment and socio-economic factors on commuting energy demand. A path analysis-based approach - Boukarta, Soufiane; Berezowska-Azzag, Ewa (Quaestiones Geographicae, 2022)
Transport is the second energy consumer sector after housing in Algeria. In this article, we explore the ener- gy implication of commuting by considering a panel of socio-economic (SE) and built environment (BE) driving factors. The method is based on four steps: (i) The first step is to identify the main and potential drivers from the literature review and to propose a model that summarises the main assumptions that could explain the volume of commuting and the resulting energy consumption. (ii) In the second step, we designed and distributed 700 questionnaires in the municipality of Djelfa and retained 184 valid questionnaires in the final study sample. (iii) In the third step, we developed a method adapted to urban areas to quantify energy consumption as a function of the distance travelled, the type and density of occupation by means of transport and the type of fuel. (iv) The fourth step is to check the fit of the hypothetical model with a path analysis-based approach. The model developed identifies 15 factors, of which five have a direct impact and 10 have an indirect impact on the energy consumption of commuting. The model shows that building density and the age of the respondent can reduce the energy consumption of commuting by up to −15% and −12% respectively; whereas the number of cars by housing and the round-trip frequency could increase the energy consumption up to 38% and 27% respectively. Our results suggest a structuring role of the socio-economic characteristics of households in explaining the energy consumption of commuting.